Acting queerly: Jonah as the implicated subject and vulnerability - G.F. Snyman (Acta Theologica)
The article poses the following question: how is queerness implicated in the Book of Jonah? Queerness is viewed more in the light of politics than identity, defining the term more in relation to power and the questioning of power than in the light of gender and sexuality. A decolonial turn is incorporated into Queer Hermeneutics. After a brief presentation of the story, the article looks at specific points of departure involved in the reading of the book: a double ethics of interpretation, vulnerability, and an implicated subject. With these in mind, the question about queerness in the Book of Jonah is discussed. The essay concludes that the spectacle of the conversion of the Ninevites constitutes a drag performance whilst Jonah’s watching of this drag performance queers himself in as much as he suffers the heat and wind while remaining silent.